Security Implications of Free Movement for Countries of the Economic Community of West African States - Adenipekun, Lawrence Olu (African Journal of Stability and Development (AJSD), 2018)
This paper examines the security implications of free movement of people in the member countries of the Economic Community of West African States (ECOWAS). In doing so, it explores the nature and dynamics of the security challenges which the Protocol on free movement has generated for the member states of this sub-regional organisation, and how these fed into and intensified the security problems bedeviling the sub-region over the past decades. The focus on the Protocol, which was adopted in 1979, is informed by the fact that it has, in the last couple of decades, been exploited by criminals to perpetrate all manners of nefarious activities, notably human trafficking, drug trafficking, small arms and light weapons trafficking, smuggling of contraband goods, cross-border armed robbery and banditry, kidnapping for ransom and terrorist activities, all of which constitute serious security concerns to the sub[1]region. It is important, for example, to note that the relative ease with which trafficking and terror gangs traverse the sub-region and carry out targeted attacks on innocent people as well as public and private facilities is directly linked to the provisions of the Protocol which, among other things, abolished requirements for visas and entry permit for Community citizens travelling within the region. The study found out that criminals travel within the region without documents as stipulated by the Protocol and illegally smuggle prohibited goods across national boundaries. It also revealed that ECOWAS does not have a computer database and this makes it difficult for border officials to document the identities of travelers, making it easier for people to commit crimes without being identified. The study discovered that this illegal movement has not only impacted negatively on human security but has also impeded intra regional efforts at ensuring security and sustainable development within the sub-region. The paper recommends that a special regular joint-border patrol should be put in place as a way of strengthening the existing collective regional security framework in West Africa. Both primary and secondary data were used for this study. Primary data were sourced through the conduct of in-depth interviews while secondary data were obtained from relevant textbooks and journals. The analysis of data generated was essentially qualitative, using descriptive and content analyses. The theoretical framework adopted for analysing this work is critical theory, which gives primacy to non-state national and transnational actors rather than making the state the primary referent of security. This theory offers more convincing explanations on how non-state criminal groups have taken advantage of the free movement Protocol of ECOWAS to perpetrate terrorism and trafficking of people and goods, with all their negative security implications.